Towards an Efficient Path to Food Security: The Philippine Case - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1998)
Government intervention is required to mitigate the pervasive market failures in the agriculture sector. However, government policies and interventions have been motivated by concerns other than the goal of long-term efficiency. The main focus of this paper is to analyze government's policy regarding property rights. Public expenditure allocation is also examined to infer how policy and institutional interventions have affected the performance of the agriculture sector. Data analysis shows that improvement on agricultural incentives happens at the expense of efficiencies of resource allocation. In addition, price distortion reduces the comparative advantage of exportable agricultural products in the world market. Inefficiencies in public expenditure allocation emanating from bureaucracy regarding organizational structure, instability in leadership, incentive problems and transitional difficulties with devolution are also traced. These, together with the detected weaknesses in property rights can guide future policy formulation.
Keywords: 330; price elasticity; price distortions